Why did so many people make so many ex post bad decisions? The causes of the foreclosure crisis - Christopher L. Foote; Kristopher S. Gerardi; Paul S. Willen (Federal Reserve Bank of Atlanta, 2012)
We present 12 facts about the mortgage crisis. We argue that the facts refute the popular story that the crisis resulted from finance industry insiders deceiving uninformed mortgage borrowers and investors. Instead, we argue that borrowers and investors made decisions that were rational and logical given their ex post overly optimistic beliefs about house prices. We then show that neither institutional features of the mortgage market nor financial innovations are any more likely to explain those distorted beliefs than they are to explain the Dutch tulip bubble 400 years ago. Economists should acknowledge the limits of our understanding of asset price bubbles and design policies accordingly.
Keywords: D14; D18; D53; D82; G01; G02; G38; 330; financial crisis; mortgage; foreclosure; asymmetric information; mortgage-backedsecurity (MBS); collaterized debt obligation (CDO); Hypothekenbank; Immobilienmarkt; Bubbles; Rationale Erwartung; Finanzmarktkrise; USA